The night before Christmas : a brick story - Moore, Clement Clarke, 1779-1863 (Skyhorse Publishing, 2015)
"Spread the Christmas cheer with this whimsical retelling of Clement C. Moore's cherished poem, "A Visit from St. Nicholas." This new edition of the classic features the text of Moore's original poem, illustrated with beautifully detailed LEGO brick scenes and characters. See the colorful stockings hung by the chimney in the fanciful brick house, and look on at the visions of dancing brick sugarplums. Turn the pages to reveal Saint Nicholas with his bundle of toys and his eight trusty reindeer, and watch as he magically slides down the chimney to bring presents to the good little girls and boys before shouting, "Now dash away, dash away, dash away all!" This treasured Christmas poem in brick will quickly become the highlight of your holiday storybooks and a great new tradition for the whole family!"--